Inclusion and online learning opportunities: designing for accessibility - Pearson , Elaine J.; Koppi , Tony (Research in Learning Technology, 2002)
Higher education institutions worldwide are adopting flexible learning methods and online technologies which increase the potential for widening the learning community to include people for whom participation may previously have been difficult or impossible. The development of courseware that is accessible, flexible and informative can benefit not only people with special needs, but such courseware provides a better educational experience for all students. DOI:10.1080/0968776020100203